A new variety of Phanera glauca subsp. tenuiflora (Leguminosae: Caesalpinioideae) from India - Kumar, Ramesh; Bandyopadhyay, Subir; Sharma, Sachin (Phytotaxa, 2014)
A new variety, Phanera glauca subsp. tenuiflora var. murlenensis, is described from Mizoram, India. <!–[if gte mso 9]> Normal 0 false false false EN-IN X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>